Biocomposite Innovation: Assessing Tensile and Flexural Performance with Maleated Natural Rubber Additives - Fatra, Warman; Anuar, Kaspul; Oktriyono, Febri Dwi; Fernando, Rivo; Helwani, Zuchra; Rusyana, Asep; Zul Amraini, Said (Heca Sentra Analitika, 2023)
Fiberglass is the most common reinforcing fiber used in composites, with polymer matrices having high tensile strength and chemical resistance, including an excellent insulating property; however, they are non-degradable. Natural fiber reinforced polymer composites have advantageous properties such as lower density and price, when compared to synthetic composite products. In addition, hybrid composites may be obtained depending on various properties such as the fibers' length, structure, content and orientation, matrix bonding and arrangement. This study was carried out to determine the effect of adding Maleated Natural Rubber (MNR) from natural rubber as a coupling agent, in order to produce the highest tensile and flexural strength. The hand lay-up and vacuum bag methods with the Response Surface Method-Central Composite Design (RSM). -CCD) were used. The composite arrangement pattern was E-glass/OPEFB/E-glass, the volume fraction of OPEFB (oil palm empty fruit bunches):E-glass was 40:60, 50:50 and 60:40, the fraction volume of OPEFB + E-glass:matrix was 40:60, 50: 50, 60: 40 and the coupling agent were added by 9, 10 and 11% of the total epoxy resin used. Furthermore, the composite mold was made of glass with dimensions of 200mm x 50mm x 50mm. The results showed that the composite product obtained from both methods had a tensile strength value, which was influenced by the variable OPEFB fiber and epoxy resin. Meanwhile, the flexural strength was influenced by the OPEFB fiber and the quadratic factor of the epoxy-MNR resin.